Children’s song media’s influence on consumption vegetables and fruits in primary school children - Aprianty, Deris; Bachtiar, Agus; Nuraeni, Irma Nuraeni (International Journal Labs, 2024)
Indonesian people consume 173 grams of fruits and vegetables per day, below the World Health Organization's recommended 400 grams. 16.54% of children aged 5-9 years do not consume vegetables and fruit, with 73.79% consuming only 1-2 portions daily. Low consumption is linked to increased risk of chronic diseases. To increase awareness, a song policy called